2011
DOI: 10.1111/j.1365-2648.2010.05580.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and patients’ perceptions of caring behaviours: quantitative systematic review of comparative studies

Abstract: papastavrou e., efstathiou g. & charalambous a. (2011) Nurses’ and patients’ perceptions of caring behaviours: quantitative systematic review of comparative studies. Journal of Advanced Nursing67(6), 1191–1205. Abstract Aim.  This paper is a report of a systematic review conducted to test the hypothesis that nurses and patients perceive the concept of caring in nursing differently. Background.  Caring is viewed as the central focus of nursing. However, despite its fundamental place in clinical practice, resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 44 publications
9
126
1
7
Order By: Relevance
“…Although not based upon focus group methodology, Papastavrou and colleagues [30] in a large survey with surgical patients and their nurses found that both patients and nurses perceived knowledge and skill as being the most important caring behaviors. However, they found differences in the importance of human presencing and respectful deference to others, whereas nurses perceived such behavior as being more important than the patients.…”
Section: Focus Group Studies On Perceptions Of Care/caringmentioning
confidence: 99%
“…Although not based upon focus group methodology, Papastavrou and colleagues [30] in a large survey with surgical patients and their nurses found that both patients and nurses perceived knowledge and skill as being the most important caring behaviors. However, they found differences in the importance of human presencing and respectful deference to others, whereas nurses perceived such behavior as being more important than the patients.…”
Section: Focus Group Studies On Perceptions Of Care/caringmentioning
confidence: 99%
“…Because it has been reported that attempts to understand students' perspectives on what they perceive as missing care are seldom presented [7] [14], the aim of this qualitative descriptive study was to explore graduate nursing and pastoral care student's perceptions of missed care in Norway.…”
Section: Purposementioning
confidence: 99%
“…In summary, the nursing profession has long been recognized as a caring profession [2,3,[32][33][34][35][36]. Rhodes [37] found that incoming nursing students identified the essential quality for the nurse is caring.…”
Section: Traditional and Non-traditional Nursing Studentsmentioning
confidence: 99%
“…Many qualities may be considered important, but the most vital quality is hat of caring as nursing has long been recognized as a caring profession [1][2][3]. Nurses have consistently been concerned with the human dimensions of healthcare and have been recognized as dealing holistically with patients [4].…”
Section: Introductionmentioning
confidence: 99%